FACIES AND GAS RESERVOIR ANALYSIS FS 2B - FS 5 INTERVAL, MOZART FIELD, KUTAI BASIN, EAST KALIMANTAN - Drieka , Ezra
Mozart Field is a giant gas and condensate field located in the Kutai Basin, East Kalimantan, with dimension of 75 km in length and 15 km in width. Since first production in 1990 to 2018, Mozart Field has become the highest cumulative gas production field in Indonesia. The study was conducted in the selected area of Mozart Field. The main objective of this research is evaluating the facies distribution in order to understand the distribution, geometry and connectivity property of gas reservoirs for further field development. The work of scope is limited to 38 available wells in the study area and research interval within the Main Zone, MFS 4, FS 2b - FS 5 (N15 - N14). Methodologies which are utilized in the study consist of facies analysis, electrofacies, depositional environment interpretation, sequence stratigraphic correlation, and probabilistic petrophysics analysis with dual water model. Core analysis at the study interval generated 9 distinctive lithofacies types, consists of 5 sandstone lithofacies and 4 siltstone and claystone lithofacies. Depositional environment at the study interval is tide-influence delta, with east to southeast sedimentation direction. Association facies are found in the form of mouth bars, distributary channels, functioned as reservoir rocks, while delta front mud and prodelta mud as seal rocks. Facies mapping process is generated by previously electrofacies interpretation for every available wells in the study area. The interpretation of facies lateral distribusion uses a deterministic sedimentology approach based on modern analog facies model of Delta Mahakam. Facies distribution maps are generated for each bedset interval within FS 2B – FS 5. acies map indicates sedimentation direction towards southeast - east direction, which controls reservoir geometry and distribution. The facies maps which previously generated will be combined with petrophysics interpretaion and pressure reservoir data in order to understand the connectivity, distribution and geometry of net pay. The inhomogeneous character of facies distribution induces reservoir compartementalization. Net pay map of interval FS 2B – FS 5 identifies 56 layer of gas reservoir, with 40 of them are connected sand, while 16 are true new sand. Facies characterization of each reservoir layers shows 20 layers of reservoir are channel type and 36 are bar type. Generally, channel resevoirs have better connectivity than bar reservoirs. Net pay map indicates hydrocarbon discovery is more common toward east direction correlating with the up dip direction and the high hydrocarbon accumulation correlates with the location of distributary channel facies in the research area.